MANUSKRIP MUSHAF AL-QUR‘AN DAUN LONTAR KOLEKSI KIAI ABDURROCHIM (KAJIAN PEMAKAIAN RASM DAN QIRA`AT) - Qona’ah Dwi Hastuti; Abdul Kholiq Hasan (Profetika: Jurnal Studi Islam, 2020)
This research is analyzing the manuscript of Al-Qur‘an on palm leaf collected by Kiai Abdurrochim from Tarub, Central Java. There is only one text being the object of the study. It is focused on how to use rasm and qira`at in the manuscript collected by Kiai Abdurrochim. The researchers found that the manuscript used usmani rasm rules in rasm writing, although there were some writing errors but they did not affect the writing. Whereas in the aspect of the qira`at of the manuscripts uses Imam Ashim’s qira`at based on the narration of Hafs in duplicating the text. Even though there are some words in certain pronunciations that still refer to Qalun’s qira`at based on the narration of Nafi’.